213k views
4 votes
-0.5g + 13 = 3g
Solve the equation

User Fractal
by
6.3k points

2 Answers

4 votes
Answer:

g = 3.7143

ฅ^•ﻌ•^ฅ
User Euther
by
6.0k points
5 votes

Answer:

13+3g=2g

We simplify the equation to the form, which is simple to understand

13+3g=2g

We move all terms containing g to the left and all other terms to the right.

+3g-2g=-13

We simplify left and right side of the equation.

+1g=-13

We divide both sides of the equation by 1 to get g.

g=-13

Explanation:

13+3g=2g

We simplify the equation to the form, which is simple to understand

13+3g=2g

We move all terms containing g to the left and all other terms to the right.

+3g-2g=-13

We simplify left and right side of the equation.

+1g=-13

We divide both sides of the equation by 1 to get g.

g=-13

User Aivis Zvezdovs
by
5.8k points